Eco-Friendly Energy Efficient Classrooms and Sustainable Campus Strategies: A Case Study on Energy Management and Carbon Footprint Reduction - Patil, Ganesh Nagraj; Tanavade, Satish Suresh (International Journal of Energy Economics and Policy, 2024)
This research paper presents a comprehensive study on energy management and carbon footprint reduction in an educational institutional campus. It focuses on implementing energy-efficient technologies and practices to minimize energy consumption and environmental impact. The study encompasses four cases, each addressing different aspects of energy use in a university setting, including the installation of LED lighting, programmable remote switches, and high-efficiency air conditioning systems. The methodology involves a detailed analysis of energy consumption patterns, using smart energy meters and theoretical calculations. Case I establishes a baseline energy consumption, while subsequent cases implement energy-saving measures. Case II involves replacing traditional tube lights with energy-efficient LED lights, resulting in considerable energy savings. Case III extends these savings further by integrating programmable remote switches mapped with student timetables. Finally, Case IV proposes the replacement of older air conditioning units with 25 SEER models, leading to significant reductions in energy use. The results highlight the effectiveness of these interventions. Case II achieves a 66.67% energy saving, while Case III yields up to 77.78% energy saving in lighting and 33.34% in air conditioning. In Case IV, the adoption of high-efficiency air conditioners can result in a 52% energy saving during teaching weeks. The economic benefits of these measures are substantial, with cost savings per classroom ranging from 7.65% in Case II to 53.46% in Case IV. Moreover, the environmental impact of these energy conservation techniques is substantial. The study reports reductions in carbon emissions from 14.71metric tons of carbon dioxide equivalent (MT CO2e) in base Case I to 6.85 MT CO2e in Case IV. The overall carbon emission reductions for Cases II, III, and IV are 7.61%, 36.37%, and 53.43%, respectively. This study demonstrates the profound impact of integrated energy management strategies in reducing the carbon footprint and energy consumption in educational institutions, offering a model for sustainable and economically viable operations.